Business Consulting: Evaluación del emprendimiento de una empresa consultora especializada en servicios energéticos integrales - Bustamante Villegas, Jorge (2024)
The feasibility of establishing a consultancy specialized in comprehensive energy services in Peru, aimed at the retail electricity market, was evaluated. Free customers have experienced an annual growth of 14.8% in recent years and at the end of 2023, there were 3,312 free users, representing only 0.04% of the total electricity users. However, there is an estimated potential of 19,701 regulated customers who could benefit from migrating to the free market, presenting an opportunity for energy consultancy. The market analysis reveals rising energy prices and a growing need for energy efficiency in companies, as well as tiny and medium-sized enterprises, which face barriers to accessing the free market due to a lack of technical knowledge and distrust of new technologies. We seek to overcome these barriers by offering an integral and personalized service that includes consulting on supply contracts (PPAs), implementation of energy solutions, and continuous advice. The business model was validated through a real experimental case, demonstrating the effectiveness of the proposed solutions and the potential for savings, achieving a 37% reduction or 14,000 soles per month in electrical costs. The financial analysis shows an Economic Net Present Value (VANE) of S/ 290,796 and an Economic Internal Rate of Return (TIRE) of 70.4%, confirming operational profitability. The Financial Net Present Value (VANF) of S/ 222,572 and the Financial Internal Rate of Return (TIRF) of 85.3% support its financial viability and value creation for shareholders. In conclusion, the creation of this consultancy is a viable and sustainable business opportunity, capable of generating economic, social, and environmental value.